2013
DOI: 10.1517/13543784.2013.828691
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in lung cancer: rationale for a combination therapy

Abstract: Future perspective studies are required in nonsmall-cell lung cancer (NSCLC) patients to better investigate the effect of metformin action on the RAS/RAF/MAPK pathway and the best context in which to use metformin in combination with molecularly targeted agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…We used 10 mM metformin in our study, which is around 200-fold higher than the plasma level of metformin in type 2 diabetic patients [27]. It seems that reaching to such levels of metformin at in vivo is impossible and even may be toxic for physiologic condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 10 mM metformin in our study, which is around 200-fold higher than the plasma level of metformin in type 2 diabetic patients [27]. It seems that reaching to such levels of metformin at in vivo is impossible and even may be toxic for physiologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Long time exposure to metformin causes the appearance of drug therapeutic effects at low concentrations. Moreover, it has been demonstrated that metformin accumulates in tissues several folds higher than in the blood and in the mitochondrial matrix it could accumulate until 1000-fold (> 20 mmol/L) [2729]. Taken together, these indicate that cell culture results of EMT inhibition by metformin are applicable for in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19]101 Although the demonstration of resistance to oncogenemediated targeted therapy through the adaptation of cellular metabolism suggests that the rewiring of cellular metabolism plays a fundamental, convergent role for oncogenes and signal transduction in promoting tumorigenesis, little is known about how the cancer signaling networks are remodeled and which pathways are invoked to sustain survival in the presence of drugs targeting central key signaling metabolic hubs (e.g., AMPK, mTOR) that respond to an array of signaling metabolic inputs and regulate a range of downstream effector metabolic pathways. Together, our current findings suggest, for the first time, that chronic adaptation to high doses of the AMPK agonist/mTOR inhibitor metformin appears to causally involve 2 highly intertwined molecular phenomena underlying enhanced cancer aggressiveness.…”
Section: P Value Ratiomentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] While it might appear intuitive that deregulated cancer metabolism can activate pro-survival signaling and decrease druginduced apoptosis to provide a general, unspecific protection against cell injuries induced by multiple types of cytotoxicities, it is worth noting that resistance to oncogene-mediated targeted therapy has been shown to require a shift toward the very same metabolic state that is controlled by growth factor signaling. 20,21 In cancer cells sensitive to lapatinib, the small-molecule dual inhibitor of the oncogenes EGFR and HER2, receptor tyrosine kinase signaling is disrupted, and activity of its Ras, PI3K, and mTOR downstream effectors is abrogated; because oncogenedependent metabolic rewiring is prevented, cancer cell death is observed.…”
mentioning
confidence: 99%
“…Once activated, this enzyme restricts anabolic processes such as protein, cholesterol, and fatty acid synthesis and inhibits mTOR, a protein kinase known to be upregulated in NSCLC. In addition, metformin reverses hyperinsulinemia, leading to downregulation of insulin-like growth factors, which promote tumorigenesis via activation of the phosphatidylinositol 3-kinase/ protein kinase B (Akt) pathway [9,11]. Finally, metabolic reprogramming from oxidative phosphorylation to aerobic glycolysis, known as the Warburg effect, is a hallmark of cancer cellsthatconveysa growth advantage.Despite this glycolytic shift, some malignant cells retain the capacity to continue oxidative phosphorylation for energy production, which could enhance malignant potential.…”
Section: Metforminmentioning
confidence: 99%